Chemical analysis of blue corn base malt and the effect of malting and roasting of blue corn malts on color and antioxidant compounds associated with antioxidant capacity - Flores-Calderón, Alex María Daniela; Hernández-Carapia, Miguel Ángel; Luna, Héctor; Escalona-Buendía, Héctor Bernardo (Emirates Journal of Food and Agriculture, 2022)
The objectives of this research were to carry out a chemical analysis of the base malts, to evaluate the effect of malting and roasting on both color and compounds associated with the antioxidant capacity (anthocyanins, phenolic compounds, melanoidins), and the capacity itself by ABTS and DPPH assays in base malt and caramel malt of blue corn. In order to provide styles of beers with different sensory characteristics as well as health benefits for the consumer, and since malt is the heart of beer, different cereals and pseudo-cereals have been malted. In addition to this, with the intention of taking advantage of the phenolic compounds present in the blue corn grain, and of developing color compounds as well as antioxidant activity through roasting, both blue corn base and caramel malts were developed. Results showed that the protein content was within the specified range for barley malt and, despite the malting not having a significant effect on the color parameters, a decrease in the anthocyanin content was observed. On the contrary, an increase in the content of phenolic acids as well as in the antioxidant capacity by DPPH assay in the base malt with respect to the grain was noticed. Additionally, the color of caramel malts increased in luminosity and chroma, and decreased in tone due to roasting. Likewise, the concentrations of anthocyanins and phenolic compounds depended on the roasting conditions. Moreover, the higher the roasting temperature was, the higher the concentrations of melanoidins were. Finally, malts that had a greater amount of phenolic compounds showed greater antioxidant capacity by ABTS assay, while malts that had a higher melanoidins content showed a greater antioxidant response by DPPH assay. In accordance with the results, it was concluded that the combined use of base and caramel malts to produce corn beer musts could provide significant amounts of compounds that will impact its color and antioxidant capacity, thereby favoring the chemical stability of the produc